Prior knowledge promotes hippocampal separation but cortical assimilation in the left inferior frontal gyrus - Oded Bein (Nature Portfolio, 2020)
Prior knowledge strongly impacts new learning, but its influence on the neural representation of novel information is unknown. Here, the authors show multiple neural codes for learning: prior knowledge leads to integrated cortical representations, while promoting hippocampal separation.